Characterization of bacteriocin production in Lactobacillus spp. isolated from mother's milk. (May 2018) - Mohammadi, Fahime; Eshaghi, Morteza; Razavi, Shabnam; Sarokhalil, Davood Darban; Talebi, Malihe; Pourshafie, Mohammad Reza
Abstract: The purpose of the present study was to isolate Lactobacillus bacteria from mother's milk and to assess their probiotic potential. Sixty breast milk samples were collected from the volunteered mothers aged from 19 to 35 and from rural areas of Lorestan and Markazi Provinces, Iran. At first, 970 bacill-shaped bacterial colonies were isolated from these samples and stored in proper condition. Two hundred isolates were randomly selected and investigated for their ability to tolerate acidic condition and to tolerate bile salt as well. Only 33 isolates could withstand the exposure to low pH and bile salt. The isolates were identified using PCR primer specific to Lactobacillus and it was demonstrated that eighteen of thirty-three isolates were belonged to the Lactobacillus . Among the isolates, 16 and 2 of them were Lactobacillus reuteri and L. gasseri, respectively. In addition, the antibiotic resistance of the isolates was determined using disc diffusion method and all of the isolates were shown to be sensitive to eight out of the twelve investigated antibiotics. Moreover, the antagonistic effect of the isolates was inspected on ten indicator pathogens. Interestingly, all of the pathogenic bacteria were inhibited by Lactobacillus isolates. In addition, to partially understand the nature of inhibition mechanism, well diffusion deployed for two randomly-selected indicator bacteria and the resulting halos of three isolates were statistically significant compared to other lactobacillus (p < 0.05). Subsequently, bacteriocin genes ( pln S, La f, gas A) were identified by PCR among the isolates. The results showed that only 2 isolates possessed the gas A gene which were in accordance with well diffusion test. Consequently, eighteen Lactobacillus isolated from breast milk samples which all of them were able to tolerate low pH and bile salt. Similarly, all of the Lactobacillus isolates were proved to inhibit the growth of pathogen strains and two of them possess a bacteriocin-related gene.